Implementasi Peraturan Daerah Kabupaten Pesisir Selatan Nomor 1 Tahun 2020 Tentang Perubahan Atas Peraturan Nomor 7 Tahun 2011 Tentang Rencana Tata Ruang Wilayah Di Kenagarian Barung Barung Balantai Selatan Kecamatan Koto Xi Tarusan Oleh Wali Nagari Terha - Nopaluwis Nopaluwis; Annisa Mardhatillah; Ariq Naufal Fathirizqi; Cici Putri Nami; Reva Daratista; Putri Juwita; Elwidarifa Marwenny (GLOBAL SCIENTS PUBLISHER, 2025)
One of the areas in Pesisir Selatan Regency, namely Barung-Barung Balantai Selatan, is prone to ecological disasters, especially landslides and floods due to deforestation and development without good spatial planning. Currently, this area is facing water infiltration problems that interfere with community activities, even though so far there has been Regional Regulation Number 1 of 2020 concerning Water Infiltration Areas as an effort to preserve the environment and optimize the function of water infiltration areas in the region, but in reality this problem still occurs. The limitations of the problems studied in this regard include: 1) the implementation of the Regional Regulation of South Pesisir Regency Number 1 of 2020; 2) obstacles or obstacles faced by the Wali Nagari in overcoming regional regulations related to Water Infiltration Areas in Kenagarian Barung-Barung Balantai Selatan Koto XI Tarusan. To unravel this problem, a type of empirical juridical research is used with a case approach (case aproach) and a statutory approach (statute aproach) so that conclusions are obtained: 1) The implementation of Regional Regulation Number 1 of 2020 in South Barung-Barung Balantai Kenagarian has not been effective because there is no Nagari Regulation on water catchment areas. After the flood on March 7, 2024, the Nagari collected residents' complaints and planned a discussion about the local regulation.They will draft Nagari Regulations with sanctions for violators. Some measures, such as building culverts and providing assistance to flood victims, have been taken. Nagari is trying to solve the problem of water catchment areas by involving residents.; 2) Inadequate development of Irrigation Areas can disrupt water catchment areas. Wali Nagari needs to protect the area.